Disiplin, keterampilan, dan lingkungan kerja guna meningkatkan efektivitas kerja karyawan - Wasis Wasis (MBR (Management and Business Review), 2021)
This study aims to determine the effect of discipline, skills, and work environment on work effectiveness. Types of primary data, data collection methods through observation, interviews, and questionnaires. The population used is employees of the production division of PT. Putra Restu Ibu Abadi has 96 employees. The sampling technique used was the saturated sampling method. Data analysis used Multiple Linear Regression. Based on the analysis and discussion, it shows that there is an effect of work discipline on work effectiveness, the more disciplined the employees of the production division work, the more effective their work will be. There is an influence of work skills on work effectiveness, the more productive employees have skills in work, the more effective the work. There is an influence of the work environment on the effectiveness of work, a good work environment, the more effective the work of production employees.